A Survey on Traction Motor and Its Prototyping Method for Electric Vehicle Application - Hari Maghfiroh; Muhammad Rizqi Subeno; Muhammad Renaldy Darmawan; Ramadhan Prihananto (Universitas Sebelas Maret (UNS), 2023)
Electric vehicle (EVs) is the main solution to reduce air pollution from the transportation sector. The main component of an EV is the propulsion system, energy storage system, and auxiliary system. The propulsion system is consisting of a motor and its drives, while the energy storage system is a battery or other energy storage and its management system. Whereas the auxiliary is like a lamp and air conditioner. This research aims to review some electric motors and their prototyping method of an EV. There are several methods for programming electric motor drives in EVs. One of the fastest solutions in fast prototyping in the motor drive of an EV is using the Hardware in the Loop (HIL) method. These papers can be used as references to determine the type of traction motor used in EVs and the method for doing rapid prototyping of it.